Mahram Pada Safar Perempuan Dalam Tinjauan Sosiologis (Menjembatani Realitas Muslim Klasik dan Kekinian) - Permana, Aramdhan Kodrat (Sunan Kalijaga State Islamic University & The Asia Foundation, 2010)
The idea of the inclusion of mahram for women travelling is an alternative and necessary instrument for the safety and comfort of women. This article anlayzes the concept ogf mahram from a sociological perspective. Socio. historically argue that the hadits of mahram was produced by the Prophet to guarantee the safety of women while they travelling. Mahram here functions like the security guard for the women. In understanding the hadith in our today's context, the rationale or